Emerging role of interleukin‐31 and interleukin‐31 receptor in pruritus in atopic dermatitis. Issue 1 (20th July 2017) - Furue, M.; Yamamura, K.; Kido‐Nakahara, M.; Nakahara, T.; Fukui, Y.
Abstract: Atopic dermatitis (AD) is a chronic or chronically relapsing, eczematous, severely pruritic skin disorder associated with skin barrier dysfunction. The lesional skin of AD exhibits T helper 2 (TH 2)‐deviated immune reactions. Interleukin‐31 (IL‐31), preferentially produced from TH 2 cells, is a potent pruritogenic cytokine, and its systemic and local administration induces scratching behavior in rodents, dogs and monkeys. Recent clinical trials have revealed that administration of an anti‐IL‐31 receptor antibody significantly alleviates pruritus in patients with AD. In this review, we summarize recent topics related to IL‐31 and its receptor with special references to atopic itch.